• Join over 1.2 million students every month
  • Accelerate your learning by 29%
  • Unlimited access from just £6.99 per month
  1. 1
  2. 2
  3. 3
  4. 4
  5. 5
  6. 6
  7. 7
  8. 8
  9. 9
  10. 10
  11. 11
  12. 12
  13. 13

Mathematical Investigation

Extracts from this document...


Type I: Mathematical Investigation

The equation of the sine function is defined as f(x) = a∙sin∙b(x+c) +d; f(x) is the function notation; a is the amplitude; sin is the function; b is the representation of the stretch factor; c represent any phase shift; d is the y intercept. (Any transformation of the sine function is compared to y=sin(x)).

Part I

Figure #1: The graph of y=sin(x)


Figure #2: Comparison of different equations of sine functions: y=sin(x); y=2sin(x); y= (1/3) sin(x); y=5sin(x).


Figure #3: Investigation of other sine graphs


Based upon Figure #1 to Figure #3, as “a” varies only the amplitude of the graph changes according to |a|. Since only the value of “a” changed, there is no change in the period, no phase shift, no change in X and Y intercepts. As these figures illustrated, every single graph plotted has the same period (period is the horizontal distance between two points on the x-axis; period usually defined as the horizontal distance along x-axis of one complete cycle, 2pi radians) and the same X and Y intersects. There is no phase shift in any of the graphs because the position of the periods and x intercepts of each graph is the same.



The transformation of the standard sine function y= a∙sin(x) by varying values of “a” only changes the standard sine function y= a∙sin(x)’s amplitude according to |a|.

...read more.


Part III

Investigate the family of curves y=sin(x+c)

Figure#5: Graphs of different functions of the family curve y=sin(x+c):y=sin(x); y=sin[x+ (pi/4)] and y=sin[x-(pi/4)].


According to Figure #5, a change in the value of “c” shifts the entire function to the right or left of the origin; this is called a phase shift. When the red graph (y=sin(x) original) is compared to the blue graph [y=sin(x+ (pi/4)), the blue graph shifted 1/4 pi to the left while the length of each period and the amplitude remained the same with y=sin(x). When the red graph (original y=sin(x)) is compared to the green graph [y=sin(x-(pi/4)], the green graph is shifted 1/4 pi radians to the right while the length of each period and the amplitude remained the same with y=sin(x).



Based upon the observation above the transformation of the basic function f(x) = a∙sin (bx+c) +d with varying values of “c” is a horizontal translation along the x-axis; the direction of the translation is dictated by the zero of “c” in the angle (bx+c). For instance the zero of (bx+c) is –c, which means a horizontal translation along the x-axis to the left; vise versa if the zero of the bracket produces +c, the translation would be towards the right. The value of this horizontal translation is the vale of “c”.

...read more.



According to Figure #11, the standard cosine graph y=cos(x) is a horizontally translated of the standard sine graph y=sin(x) to the left by pi/2 radians. To test this hypothesis the standard cosine graph is shifted pi/2 radians to the right in the equation y=cos(x-(pi/2)) and this graph is compared to the standard sine graph. If y=cos(x) is nothing but a horizontal translation of pi/2 radians to the left of y=sin(x), then sin(x) =cos(x-(pi/2)).

Figure #12: Graphs of the function y=cos(x-(pi/2)) and y=sin(x)


According to Figure #12, the standard sine graph y=sin(x) = a horizontally translated to the right by pi/2 radians of the standard cosine graph y=cos(x). Based upon the Figure #11 and Figure #12, I conclude that cosine graph has the same amplitude and period/complete cycle as the standard sine graph; cosine is horizontally translated pi/2 radians to the left in reference to y=sin(x).

Based upon the properties observed two relations are obtained:

sin (x)=cos(x-(pi/2))

cos (x)=sin(x+(pi/2))

By combining the properties of the reflection on the x-axis and translation by the standard sine function y=sin(x), the standard cosine function y=cos(x) can also be obtained.

Figure #13: Graph of y=-sin(x-(pi/2)) and y=cos(x)


According to Figure # 13, the reflection on the x-axis with horizontal translation to right (by pi/2) by the sine function is the same as y=cos(x). Therefore based upon the properties gathered from Figure #13, two relations are obtained:

cos (x)=-sin(x-(pi/2))

sin (x)=-cos(x+(pi/2))

...read more.

This student written piece of work is one of many that can be found in our AS and A Level Core & Pure Mathematics section.

Found what you're looking for?

  • Start learning 29% faster today
  • 150,000+ documents available
  • Just £6.99 a month

Not the one? Search for your essay title...
  • Join over 1.2 million students every month
  • Accelerate your learning by 29%
  • Unlimited access from just £6.99 per month

See related essaysSee related essays

Related AS and A Level Core & Pure Mathematics essays

  1. Marked by a teacher

    The Gradient Function

    5 star(s)

    Here, it is a little hard to prove this in the normal sense as (x+h) is square rooted, so I will need to rationalize the numerator. V (x+h) - Vx = V (x+h) - Vx x + h -x h V (x+h)

  2. Marked by a teacher

    Estimate a consumption function for the UK economy explaining the economic theory and statistical ...

    3 star(s)

    The most commonly one is the permanent income theory. It states that consumer determines their consumption on the basis of a longer view available, taking into account not just current income but future expected income and any change in the value of their wealth. It gives rise to a consumption function of the form: ct =c0+c1ytp Fits the data

  1. Sequences and series investigation

    - 12 +1 3. 72 - 12 + 1 4. 72 - 11 5. = 61 Successful Sequence 8: 1. 2(82) - 16 + 1 2. 2(64) - 16 + 1 3. 128 - 16 + 1 4. 128 - 15 5.

  2. Maths - Investigate how many people can be carried in each type of vessel.

    y (AE-DB) + z (AF-DC) = AK-DJ (iv) multiply by (IA-CG) => y (AE-DB)(IA-CG) + z (AF-DC)(IA-CG) = (AK-DJ)(IA-CG) y (HA-BG) + z (IA-CG) = AL-JB (v) multiply by (AF-DC) => y (HA-BG)(AF-DC) + z (AF-DC)(IA-CG) = (AF-DC)(AL-JG) Subtract: (v) - (iv) => y (HA-BG)(AF-DC) - y (AE-DB)(IA-CG) = (AF-DC)(AL-JG)

  1. Experimentally calculating the wavelength of an He-Ne laser by means of diffraction gratings

    Percent Error = abs((632.8 - 686)/632.8)100% Percent Error � 8.41% 3rd Fringe Percent Error = abs((theoretical value - experimental value)/theoretical value)100% Percent Error = abs((632.8 - 692)/632.8)100% Percent Error � 9.36% So, the percent error never goes beyond around 33%.

  2. Triminoes Investigation

    So these results would help met to find out the relationship. The Formula for the n th term f (n) =an� + bn� +c Quadratic (3 unknown) f (n) =an� + bn� + cn� + d Cubic (4 unknown) f (n)

  1. Investigation into combined transoformations of 6 trigonometric functions

    The d value changes the y value of the co-ordinates; the value seems to rotate the graph around the point where the graph passes through the x-axis. From this I conclude the graph is translated first then is rotated. The fourth combined transformation I'm going to be looking at will

  2. Investigation of the Phi Function

    iv ?(6) = {1, 5} = 2 v ?(25) = {1, 2, 3, 4, 6, 7, 8, 9, 11, 12, 13, 14, 16, 17, 18, 19, 21, 22, 23, 24} = 20 Part 2 a) i ?(7 x 4) = ?(28) = 12 ?(7) x ?(4) = 6 x 2 = 12 Thus, ?(7 x 4)

  • Over 160,000 pieces
    of student written work
  • Annotated by
    experienced teachers
  • Ideas and feedback to
    improve your own work